Design Web-based Portal to Management a Pilgrim Office in Kurdistan Region - Sabri, Shaimaa Q.; Arif, Jahwar Y.; Taqa, Ghada Abd Alrhman; Çinar, Ahmet (The Indonesian Journal of Computer Science, 2024)
In the era of globalization, the region of Kurdistan, is participation in several ongoing projects where IT-enable systems are intended to be implemented in various sectors as part of the national IT policy. However, because of the establish system complex structure and the outdated system poor design, implementing IT enable systems locally is a significant issue. Particularly in the section dedicated to Hajj services, where files are still manually stored overcrowding happens ate registration offices since pilgrims cannot get any fresh instruction or announcements at the time they must got to the office or call them and insufficient security and safety measure for pilgrims’ data. The purpose of developing this file filing system was to facilitate and ease the management of current files by staff. As part of the research process, issues with Haji file management were identified and information was gathered via literature research, interview and observation. Laravel (PHP), Bootstrap and HTML5 are programming language used in system development, along MySQL, Xampp. System Usability Scale (SUS) approach was used to test the system, and 10 participations sign up for it. The highest overall satisfaction rate, at roughly 80.1%